Clinical and Basic Research Progress on Treg-Induced Immune Tolerance in Liver Transplantation - Ni, Xuhao; Wang, Qi; Gu, Jian; Lu, Ling (Frontiers in Immunology, 2021)
Rejection after organ transplantation is the main cause of graft failure. How to effectively reduce rejection and induce tolerance was still a difficult issue in the field of transplantation immunology. Although the liver, as an immunologic privileged organ, is more susceptible to spontaneous and operational tolerance after transplantation, which could maintain its normal function for a longer time. Modern immunosuppression regimens have serious toxicities and side effects. There is huge risk of blindly stopping immunosuppression regimens. It is the Holy Grail to find more effective treatments to induce immune tolerance. Tregs have been shown to play a pivotal role in theregulation of immune balance, and infusion of Tregs can also effectively prevent rejection and cure autoimmune diseases without significant side effects. According to liver immune characteristics, the correct use of Tregs in patients with liver transplantation can more effectively induce the occurrence of operational tolerance than other organ transplants. This review mainly summarizes the latest research advances about the characteristics of immune microenvironment of liver, operational tolerance, Tregs generation in vitro, and the application of Tregs in liver transplantation. It is hoped that this review will provide a deeper understanding of Tregs as the main effective treatments to induce and maintain operational tolerance after liver transplantation.